Por uma educação católica : um estudo sobre a disciplina religião no Ginásio Santa Teresinha (1947-1968) - Rodrigues, Simone Paixão (2008)
The present work focuses the discipline Teaching Religious given in the Gymnasium Santa Teresinha, in the period from 1947 to 1968, searching to infer on the use of that curricular component while instrument of propagation of the catholic faith. This written production follows a coherent metodológical way with the research field history of school disciplines and its estimated theoreticians, articulated the analysis of written sources and prays. The choice for the study of that school disciplines intervien that establishment was stimulated by two reasons: first, for the necessity to understand the catholics strategies for the maintenance of its hegemony in the social and cultural field of the country; second, for the great necessity to extend the studies inside of the field of the history of the school disciplines.